Sedimentation of Magnetic Suspensions of Magnetite - Yang, X.; Aldrich, Chris (Bentham Science, 2008)
The gravity sedimentation of three narrow-sized fractions of suspensions of magnetite particles exposed to magnetic fields ranging from 0 to 180 x 10-4 T was studied experimentally. At volumetric solids concentrations in excess of 15%, the magnetized suspensions of magnetite with size fractions ranging from -75 to +38 µm settled more slowly than the non-magnetized suspensions. However, owing to relatively weak magnetic interaction, the sedimentation of the magnetized and non-magnetized -38 µm size fractions was similar.